Vem är ”en riktig älvdaling”? Identitetsmarkörer i dagens Älvdalen - Melerska, Dorota (Folia Scandinavica Posnaniensia, 2010)
The article is a short analysis of the concept of identity among the population of Älvdalen Municipality and the role of the local dialect Övdalian as an indicator of this identity. The population of Älvdalen Municipality is a clear example of a language group, rather than an ethnic group, which is one of the reasons why Övdalian has not been recognized as a minority language according to the The Framework Convention for the Protection of National Minorities and European Charter for Regional or Minority Languages. The local vernacular has lost its former major significance as the carrier of identity and plays nowadays merely a symbolic role. To be “a member of the Övdalian community” is associated today more with the sense of common ancestry and tradition than with the ability of speaking the local vernacular. On the other hand, people from Älvdalen Municipality consider Övdalian as the major factor that unites them.